La eficacia de las politicas publicas en Ecuador hacia el sector economico social-solidario - Minadeo, Giovanni (2014)
Social Economy, Solidarity Economy, Civil Economy, Relational Economics, Social Market Economy, Popular and Solidarity Economy, are all different terms for different currents that philosophy of economics has conceptualized differently at different times. All these concepts, whose boundaries are sometimes nebulous, have an important common component, a threshold below which are identified and support them. This threshold is called civil society, and the starring role playing, clearly mark the difference with the private and the public economy. Making a small historic route, which is not exhaustive, we see the origins of the Social Economy in Europe and its reception in Ecuador in the early twentieth century to the present real ity, with its Popular and Solidarity Economy. The last part is the result of an investigation of the Organic Law of the Popular and Solidarity Economy of 2011, through which public policies are analyzed to this sector and its effectiveness, the role of the state and its relationship with civil society.